Corpos-vozes nas cenas de vidas guineenses - BETINHA YADIRA AUGUSTO BIDEMY (2024)
This thesis sought to present, through diverse narratives produced in Guinea-Bissau, a space to discuss and reflect on the relationships between literary and cultural knowledge constructed in institutional environments or outside them, with an emphasis on productions produced by women, especially Odete Semedo and Domingas Samy. Odete Semedo is a poet active in issues related to female otherness, the political life of the country and the rights of Guinean women. Domingas Samy also turns her attention to female otherness and the traditions of the Guinean people. She was the pioneer of having published the first prose work in Guinea-Bissau – the book of short stories ,the School, in 1993, a work with which we discuss in this thesis, drawing attention to issues such as Portuguese colonialism and arranged marriages. We demonstrate the relevance of the African Party for the Independence of Guinea and Cape Verde (PAIGC) and, above all, the participation of women in the armed struggle, especially Carmem Pereira and Titina Silá, former combatants who were emblematic figures within the PAIGC, with Titina today considered a national heroine of GuineaBissau. The narratives of former combatants, together with the narratives of ordinary women from everyday life, together with the narratives of Guinean literary women, appeared side by side in this thesis as important elements in the construction of scenes of women's lives in Guinea-Bissau. This is why theories related to orature, oral literature, and Ubuntu ethics and philosophy were important to our reflections in this thesis. We tried to demonstrate with this research that thinking about literature separately from politics is a difficult task in any situation, especially when it comes to literature produced in former colonial African countries under the rubric of black women. In this way, the bodies-voices, the bodies-texts of this thesis are naturally constituted as political bodies. My research hypothesis, therefore, focuses on the proposal to read the bodies-voices of Guinean female scenes as movements of epistemic disobedience, in which I privilege productions and knowledge from the academic universe and also from outside it. A hypothesis that sustains that Guinean literary and cultural productions, even if they do not propose to be political, once they are in a place of resistance, of epistemic disobedience, are narratives that position themselves as political. This is what I defend, because they are produced, for the most part, in a non-hegemonic language, in an ancestral ethnic or Creole language, in short, in a language that is not that of the colonizer. Productions by female authors engendered in a society that is still guided by masculine values, therefore, the dialogue with these works is also political. A politics of the feminine.